CD70-mediated CD27 expression downregulation contributed to the regulatory B10 cell impairment in rheumatoid arthritis. (March 2020) - Shi, Lianjie; Hu, Fanlei; Zhu, Lei; Xu, Chuanhui; Zhu, Huaqun; Li, Yingni; Liu, Hongjiang; Li, Chun; Liu, Na; Xu, Liling; Mu, Rong; Li, Zhanguo
Highlights: The proportion of CD19 + CD24 hi CD27 + regulatory B10 (Breg) cells and their IL-10 expression were decreased in RA patients. The impairment of Breg cells might be partially attributed to the decreased expression of CD27 induced by the upregulated CD70 expression. TNF-α and IL-1β decreased the proportion of Breg cells also by upregulated CD70 expression. The proportion of Breg cells could be restored by blocking the CD70-CD27 interaction with an anti-CD70 antibody. Abstract: Regulatory B10 cells have been shown to exhibit impaired functions in autoimmune diseases. However, the underlying mechanism is still obscure. In the present study, we aimed to understand the regulatory characteristics of regulatory B10 cells and how these cells are involved in the development of rheumatoid arthritis (RA). Here, we chose CD19 + CD24 hi CD27 + as the phenotype of regulatory B10 cells. We found that the frequencies of CD19 + CD24 hi CD27 + regulatory B10 cells were decreased and that their IL-10-producing function was impaired in patients with RA compared with healthy controls (HCs). The impairment in CD19 + CD24 hi CD27 + B10 cells was partially attributed to the decreased expression of CD27 induced by the upregulated CD70 expression on CD19 + B cells and CD4 + T cells. The proportion of CD19 + CD24 hi CD27 + regulatory B10 cells could be restored by blocking the CD70-CD27 interaction with an anti-CD70 antibody. Furthermore, the CD70-CD27 interaction significantly elevated IL-10 expression and might compensate for the decreased number of CD19 + CD24 hi CD27 + B cells. Hence, the CD70-CD27 interaction might play a critical role in the numerical and functional impairments of regulatory B10 cells, thus contributing to RA pathogenesis. In conclusion, the change in CD19 + CD24 hi CD27 + regulatory B10 cells in RA was only a consequence, not the cause, of RA development, but the increased expression of CD70 might be the culprit.